The Role of Sustained Low-Efficiency Dialysis (SLED) in the Intensive Care Unit - Rita Vicente; Ricardo Santos; Silvia Coelho (Publicações Ciência e Vida, 2022)
Renal replacement therapies are frequently used in the intensive care unit, most often in patients with severe acute kidney injury, a common complication in this setting. The choice of a prolonged intermittent renal replacement therapy (PIRRT) has grown in its popularity. Nevertheless, not all clinicians are familiar with it. The most frequently performed PIRRT is sustained low-efficiency dialysis. The aim of this article is to review the sustained low-efficiency dialysis technique, namely the necessary machinery, the prescription specificities, its complications and the particularities related to intoxications and drug dosing. Lastly, when to start sustained low-efficiency dialysis and its advantages and disadvantages over intermittent hemodialysis and continuous renal replacement therapies is discussed.